CRISPR-cas subtype I-Fb in Acinetobacter baumannii: evolution and utilization for strain subtyping. - Nabil Karah; Ørjan Samuelsen; Raffaele Zarrilli; Jason W Sahl; Sun Nyunt Wai; Bernt Eric Uhlin (PLoS ONE, 2015)
Clustered regularly interspaced short palindromic repeats (CRISPR) are polymorphic elements found in the genome of some or all strains of particular bacterial species, providing them with a system of acquired immunity against invading bacteriophages and plasmids. Two CRISPR-Cas systems have been identified in Acinetobacter baumannii, an opportunistic pathogen with a remarkable capacity for clonal dissemination. In this study, we investigated the mode of evolution and diversity of spacers of the CRISPR-cas subtype I-Fb locus in a global collection of 76 isolates of A. baumannii obtained from 14 countries and 4 continents. The locus has basically evolved from a common ancestor following two main lineages and several pathways of vertical descent. However, this vertical passage has been interrupted by occasional events of horizontal transfer of the whole locus between distinct isolates. The isolates were assigned into 40 CRISPR-based sequence types (CST). CST1 and CST23-24 comprised 18 and 9 isolates, representing two main sub-clones of international clones CC1 and CC25, respectively. Epidemiological data showed that some of the CST1 isolates were acquired or imported from Iraq, where it has probably been endemic for more than one decade and occasionally been able to spread to USA, Canada, and Europe. CST23-24 has shown a remarkable ability to cause national outbreaks of infections in Sweden, Argentina, UAE, and USA. The three isolates of CST19 were independently imported from Thailand to Sweden and Norway, raising a concern about the prevalence of CST19 in Thailand. Our study highlights the dynamic nature of the CRISPR-cas subtype I-Fb locus in A. baumannii, and demonstrates the possibility of using a CRISPR-based approach for subtyping a significant part of the global population of A. baumannii.